Nonlinear Deformation of Structure Elementsfrom Different Materials under Impulse and Shock Loads - Vorobiev, Yu. S.; Kruszka, L.; Ovcharova, N. Y. (NTU "KhPI", 2016)
simulation of high-rate deformation processes, three-dimensional models are used. The following determined relationships are taken into account: elastic-plastic deformation (according to the theory of dynamic plastic deformation); the dynamic properties of the materials, which change during deformation; the finite displacements and deformations. The problem is solved by the finite elements method. The paper analyzes the impact of pulse and shock loads performed on the elements of various constructions made of different materials. Comparison of the research results shows that the elements from the improved composite material possess both the required strength and lowest weight. Furthermore, the experimental and numerical results are compared as an example of the influence of the impulse load on the composite material plate with a cut. The paper shows the features of the distribution and localization of the stress intensity and displacements at the impulse and impact loading in the multi-layered structural elements. The deformation processes occur in different stages up to the elastic-plastic finite deformations depending on the speed of the projectile. The results of these studies were used in the analysis of the dynamic strength of real structural elements.
Keywords: high-rate deformation; shock loads; finite elements method